Taboo As A Character Education Means - Ringgi’, Ismail Banne (LPPM IAKN Tarutung, 2023)
People always crave harmony in their daily lives through harmony with God, others and other creatures. In order to maintain this harmony, in society, rules that should not be violated are passed down from one generation to the next. Taboo can be a means to develop the character of everyone in society. Unfortunately, in today's Toraja society, it seems that taboo is no longer being cared for. There is a lot of disharmonies with God, fellow beings, and other creations. Taboo is regarded as just a myth that does not make sense or the boast of parents to scare children into doing what their parents want. So, how can this taboo become a means of character building? By using a qualitative-descriptive method, it was found that taboo became a means of character education through strict enforcement in people's lives through the provision of strict sanctions, exemplary parents, habituation, and strict enforcement of taboo.